2013
DOI: 10.1021/la400397q
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Metal Nanoparticle Multilayers with Polyphenylene Dendrimer/Gold Nanoparticles via “Click” Chemistry

Abstract: Multilayer films composed of azide-functional polymer and polyphenylene dendrimer-stabilized gold nanoparticles with alkynes in their peripheries have been fabricated using a layer-by-layer (LBL) approach via "click" chemistry. This method permits facile covalent linking of the polymer/nanoparticle interlayers in the mixture of DMF and water, which provides a general and powerful technique for preparing uniform nanoparticle (NP) thin films. The deposition process is linearly related to the number of bilayers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…Li et al reported stable immobilization of dendrimer structures through LbL assembly between azide-functional polymer and polyphenylene dendrimer-stabilized gold nanoparticles with alkynes at their peripheries ( Figure 8). 266 Reduction of chloroauric acid (H[AuCl 4 ]¢3H 2 O) by sodium borohydride in the presence of polyphenylene dendrimer as the stabilizing thiol ligand resulted in polyphenylene dendrimer-capped gold nanoparticles. Subsequently, azide-functionalized PAA and the dendrimergold nanoparticles were fabricated into multilayer films by LbL assembly coupled with click chemistry.…”
Section: Materials Aspectsmentioning
confidence: 99%
“…Li et al reported stable immobilization of dendrimer structures through LbL assembly between azide-functional polymer and polyphenylene dendrimer-stabilized gold nanoparticles with alkynes at their peripheries ( Figure 8). 266 Reduction of chloroauric acid (H[AuCl 4 ]¢3H 2 O) by sodium borohydride in the presence of polyphenylene dendrimer as the stabilizing thiol ligand resulted in polyphenylene dendrimer-capped gold nanoparticles. Subsequently, azide-functionalized PAA and the dendrimergold nanoparticles were fabricated into multilayer films by LbL assembly coupled with click chemistry.…”
Section: Materials Aspectsmentioning
confidence: 99%
“…[29][30][31][32] Due to their high flexibility and deformability , well ordered NP assemblies can still be formed even in systems having larger size/shape distribution discrepancies. Previous reports on nanoparticle-cored dendrimers prepared directly in the presence of dendrimers 33 or via solvent-mediated dendritic ligand exchange reaction [34][35][36][37] have included the study of spacing-dependent dipolar interactions in 2D arrays of iron oxide NPs, 38 liquid-crystalline selfassemblies of dendronized gold nanoparticles, [39][40][41] construction of covalently bound dendrimer-NP multilayers, 42 and the use of dendronized hybrid systems in drug delivery, [43][44][45] imaging and theranostics, 46 …”
Section: Introductionmentioning
confidence: 99%
“…The covalent crosslinking of multilayers oen requires the multilayers to have specic reactive species built in. Although the construction of LbL PAMAM multilayers using covalent interactions has been reported, their application in retarded release systems has not been seriously considered, [33][34][35] and the inuence of covalent crosslinking on retarded release in such multilayers requires further study. The development of strategies for simultaneously achieving covalent crosslinking of the multilayers and incorporating drug reservoirs will greatly assist the application of these multilayers in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%